Dzielimy się doświadczeniemApplication of multirow spiral computed tomography in angio mode for evaluation of left brachiocephalic vein stenosis in a haemodialised patient after haemodialysis catheter placement – case report - Legaszewski, Tomasz; Głowacki, Jan; Kusa, Jacek; Szkutnik, Małgorzata; Wasilewski, Jarosław; Trzeszkowska-Rotkegel, Sylwia; Sraga, Wojciech; Białkowski, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Together with more common use of central venous access, complications should be taken into account. Complications following central venous access can occur because of the procedure itself or due to catheter presence in the vein. The aim of the study is presentation of multirow spiral computed tomography in diagnosing complications after central access catheter application in the form of left brachiocephalic vein stenosis. The authors describe acute and chronic complications, paying special attention to the diagnostic value of multirow computed tomography. It allows determination of precise diagnosis and definition of indications for further treatment and introduction of invasive catheter therapy procedure